Hemangiopericytoma of the Gingiva – A Case Report - Sushruth Nayak; Sandhya Shrivastava; Prachi Nayak; Kush Pathak (Institute of Medico-legal Publications Pvt Ltd, 2021)
Hemangiopericytoma (HPC) is a very rare tumor with uncertain malignant potential. It is a soft tissuetumor which originates from the pericytes in the walls of the blood capillaries. Both benign and malignantvarieties are present with the tendency to metastasize. It was first described by Stout and Murray in 1942.The incidence of occurrence in oral cavity is very rare. We report a case of 57 year old male, who presentedwith an exophytic overgrowth from the lingual aspect of the maxillary left gingiva which extended into thepalatal area. The tumor was completely removed with wide surgical excision. The histopathological studyof the tumor suggested the HPC.